Empowerment of Relocation Community Affected by Covid 19 Pandemic in DKI Jakarta with Collaborative Governance - Mawar Mawar; Soesilo Zauhar; Endah Setyowati; Suryadi Suryadi; Dini Gandini (Iapa Proceedings Conference, 2021)
The covid-19 pandemic that has hit the world and Indonesia in particular is not only about the number of people exposd to the virus, but its impact on the economic life of society and the country. The slowdown in various economic activities, the business world, trade and various elements driving the real economy have led to a potential decline in the per capita income of the Indonesian population. This is what is felt by the people of the suburbs at the Rawabebek rusunawa DKI Jakarta who really depend on micro-enterprises for their living. They have experienced a decrease in income since the COVID-19 pandemic so they have limitations in meeting the needs of daily life. For this reason, sustainable community empowerment efforts are needed through aapproach Collaborative Governance. The purpose of this study is to analyze empowerment programs that have been carried out for communities affected by the COVID-19 pandemic through collaborative governance. This study uses a qualitative approach to the type of phenomenological research. The results showed that the collaboration process in empowering the relocation community at the Rawabebek flats only touched on the instrumental aspects and had not touched the substantial aspects. The collaborative process in empowering relocation communities should be based on social capital.capital Socialis capital that can be used as the driving force in empowerment. Social capital provides support to the community to take action together and reciprocally. Social capital is an alternative form of modality that is beneficial for the community to obtain both economic and social benefits.